Analysis of the Health of the Public Organization Department of Investment and Integrated One-Stop Services of Buleleng Regency - I Made Kuta; Ida Ayu Putu Sri Widnyani; Nyoman Diah Utari Dewi (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2024)
The research focuses on analyzing the health of the public organization at the Investment and Integrated One-Stop Service Office (DPMPTSP) of Buleleng Regency. It emphasizes the significance of organizational health in accomplishing development objectives and ensuring high-quality public services. Purpose The purpose of this research is to assess the public organizational health of DPMPTSP in Buleleng Regency, identify factors that hinder organizational health, and evaluate strategies to enhance organizational health. Research methodology This research use descriptive analysis with a qualitative approach. Data collection methods include observation, interviews, documentation studies, and online searches. Results The findings indicate that DPMPTSP encounters challenges related to productivity, adaptation, employee motivation, coordination, leadership, and organizational culture. These aspects are found to be suboptimal and require attention for improvement. The limitations of this research may include potential biases in data collection, limited generalizability of findings beyond the context of PMPTSP in Buleleng Regency, and constraints associated with the qualitative research approach. This research contributes to the understanding of organizational health in the context of public organizations, specifically focusing on DPMPTSP in Buleleng Regency. It identifies key challenges and provides recommendations for improving organizational health, which can ultimately enhance public services and contribute to economic growth and community welfare